1933
DOI: 10.1017/s0007485300035458
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Abundance, Distribution and Feeding Habits of some West African Mosquitos

Abstract: Almost all of the studies here reported were made in one small region, so that very little new information was secured on the ranges of the species of mosquitos under consideration.Our investigations regarding breeding-places were limited to a few species. Aëdes vittatus was found occasionally breeding in tree-holes in Ibadan. Aëdes irritans adults were taken at Ibadan, which is so far inland that this species must sometimes breed in places other than crab-holes at the edges of salt or brackish water. We did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
3

Year Published

1942
1942
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 10 publications
5
42
3
Order By: Relevance
“…Sylla et al reported Aaf domestic indoor larval habitats in Senegal. This is consistent with earlier reports from Nigeria and Gabon (Dunn , Kerr , Mattingly ,, Service , ). Furthermore, in our collections from treeholes in PK‐10 we recovered an abundance of Aaa .…”
Section: Discussionsupporting
confidence: 93%
“…Sylla et al reported Aaf domestic indoor larval habitats in Senegal. This is consistent with earlier reports from Nigeria and Gabon (Dunn , Kerr , Mattingly ,, Service , ). Furthermore, in our collections from treeholes in PK‐10 we recovered an abundance of Aaa .…”
Section: Discussionsupporting
confidence: 93%
“…T. uniformis shows a very distinct peak at 9 p.m., T. africanus from 9 to 11 p.m. This is in agreement with Kerr's (1933) work in West Africa. After passing the peak period, catches of both species decline steadily till 6 a.m. (Tables X, XI & Figs.…”
Section: Anopheles Funeslussupporting
confidence: 91%
“…those which fed the previous night, still contain a lot of blood, and may easily be confused with freshly fed females unless closely examined. Kerr (1933) in West Africa found that "gambiae" (almost certainly mixed gambiae and melas) were most active from midnight onwards.…”
Section: Feeding Activity At Nightmentioning
confidence: 99%